Challenges and Personal Protective Equipment among Healthcare Professionals during the COVID-19 Pandemic - Arazoo Issa Tahir; Masood Abdulkareem; Fatima Mohammed (Medical Journal of Babylon)
Background: The last line of defense against risks is frequently regarded as personal protective equipment (PPE). Therefore, there is a shortage of PPE in places with high demand because of COVID-19’s widespread nature. Objective: The aim of the study was to address the shortage of personal protective equipment (PPE), as well as to identify factors that increased the risk of mental health problems among healthcare workers during coronavirus disease 19 (COVID-19). Materials and Methods: A cross-sectional study was conducted from June 22nd to August 22nd, 2020, in Iraqi Kurdistan region. A total of 337 healthcare professionals participated in an online survey that included questions about socio-demographic information, personal protective measures, and risk factors for mental health issues. SPSS software version 24.0 was used to analyze data. Results: The majority of healthcare professionals 196 (58.2%) were men. The majority of the population was aged 25–34 years 211 (62.6%), with nursing, representing the highest percentage among all professions 151 (44.8%). At least 46.6% of the participants reported a lack of PPE. The most common shortages reported were hats, boots, N95 masks, goggles, and face shields. A significant positive correlation (r = 0.181, P = 0.001) was observed between direct contact with COVID-19 patients and the spreading of fear and panic among healthcare professionals due to their concerns about transmitting the virus to their relatives. Also, results revealed that healthcare professionals’ non-receive training on the ways of facing the COVID-19 crisis was another risk factor affecting healthcare professionals’ mental health in all hospitals (r = 0.119, P = 0.001). Conclusion: According to the current study, healthcare professionals lacked the resources needed to treat COVID-19 patients. To avoid healthcare professionals’ mental health problems during medical emergencies, the government should take action, especially the Ministry of Health, which should address the challenges in the case of a future health crisis.